Audio-visual Development : Composed Song Through Dolanan Song to Improve Learning Outcomes of Writing Aksara Jawa Pasangan - Dwi Astuti; Deni Setiawan (JETL (Journal of Education, Teaching and Learning), 2025)
The purpose of carrying out this research and development is to produce composed song learning media products through Dolanan song and audio-visual based that have been tested for feasibility, so that they are effective in improving the learning outcomes of sixth grade students on the material of writing aksara Jawa pasangan that researched at Pesantren State Elementary School, Mijen, Semarang City. Using research and development models from Borg and Gall covering potential and problem stages, data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision, and mass production. The instruments are questionnaires for teacher and student needs; media and material expert validation questionnaire; questionnaire of teacher and student responses; and pretest-posttest questions. The media due diligence uses the percentage of eligibility criteria obtained from the results of expert validators, teacher responses, and student responses. The media effectiveness test is using the criteria of increasing the average value based on the N-Gain formula obtained from the pretest and postest values. The result is that this product is very feasible for use in usage trials with a percentage of 94.68% of media expert validators; 93.05% of material experts; 94.4% of teachers' responses; and 95.9% of student responses. The N-Gain test result is 0.55; So that the product has been effective in improving student learning outcomes with moderate improvement criteria.